2007
DOI: 10.1093/rheumatology/kem018
|View full text |Cite
|
Sign up to set email alerts
|

Trends in economic consequences of rheumatoid arthritis over two subsequent years

Abstract: In particular, costs for devices/adaptations and for medication changed during follow-up. The latter was probably due to an increase in the use of biological agents. Hopefully a decrease in direct costs and a reduced percentage of patients getting work disabled by better disease control will outweigh the high costs of biological drugs in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The studies that adopted the incidence-based approach, focused on recent-onset patients and were primarily conducted in a European setting. [14][15][16][17][18][19][20][21] Cost components and measurement of direct or indirect costs also varied markedly due to the aims and data availability among studies. Twenty-seven studies reported both direct and indirect costs, while 36 studies and 9 studies reported direct and indirect costs only, respectively.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…The studies that adopted the incidence-based approach, focused on recent-onset patients and were primarily conducted in a European setting. [14][15][16][17][18][19][20][21] Cost components and measurement of direct or indirect costs also varied markedly due to the aims and data availability among studies. Twenty-seven studies reported both direct and indirect costs, while 36 studies and 9 studies reported direct and indirect costs only, respectively.…”
Section: Methodological Approachesmentioning
confidence: 99%
“…The addition of biological agents in treatment strategies for RA have improved the possibility of controlling disease activity510 and slowing the progression of joint damage 11. However, the prices of these drugs are high and several studies have proved that the use of these medications increases the overall (direct) healthcare costs of RA, despite savings in cost categories such as hospitalisation 312–14. On the other hand, it is known that the indirect costs of RA exceed direct healthcare costs.…”
mentioning
confidence: 99%
“…Frequency distribution of the patient's responses to selected knowledge and attitude items (patient's perspectives and awareness). literatures; Jorit et al [9] and Verstappen et al [10] who found that the majority of cases were females (86%) with a median age of (53) year. Housewives formed (64%) of the study sample, quite different from western countries, this obviously is due to the differences in cultural and environmental factors between our society and the western societies [4] [5].…”
Section: Discussionmentioning
confidence: 98%